Relationships between perceived family gambling and peer gambling and adolescent problem gambling and binge-drinking - Zhai, Zu Wei (J Gambl Stud, 2017)
PURPOSE: The study systematically examined the relative relationships between perceived family and peer gambling and adolescent at-risk/problem gambling and binge-drinking. It also determined the likelihood of at-risk/problem gambling and binge-drinking as a function of the number of different social groups with perceived gambling. METHODS: A multi-site high-school survey assessed gambling, alcohol use, presence of perceived excessive peer gambling (Peer Excess – PE), and family gambling prompting concern (Family Concern – FC) in 2,750 high-school students. Adolescents were separately stratified into: 1) low-risk, at-risk, and problem/pathological gambling groups; and, 2) non-binge-drinking, low-frequency -binge-drinking, and high-frequency-binge-drinking groups. RESULTS: Multinomial logistic regression showed that relative to each other, FC and PE were associated with greater likelihoods of at-risk and problem/pathological gambling. However, only FC was associated with binge-drinking. Logistic regression revealed that adolescents who endorsed either FC or PE alone, compared to no endorsement, were more likely to have at-risk and problem/pathological gambling, relative to low-risk gambling. Adolescents who endorsed both FC and PE, compared to PE alone, were more likely to have problem/pathological gambling relative to low-risk and at-risk gambling. Relative to non-binge-drinking adolescents, those who endorsed both FC and PE were more likely to have low- and high-frequency-binge-drinking compared to FC alone or PE alone, respectively. CONCLUSIONS: Family and peer gambling individually contribute to adolescent at-risk/problem gambling and binge-drinking. Strategies that target adolescents as well as their closely affiliated family and peer members may be an important step towards prevention of harm-associated levels of gambling and alcohol use in youths.